Assessing trends and drivers of burned areas in forest areas in the Kurdistan Region - Azad Rasul; Ismahil Shkur Zahir (Environmental Monitoring and Assessment, 2026)

Phytochemical composition, antioxidant, and antibacterial potential of three brown seaweeds from Japan - Faria Afrin; Md. Apon Dulal; Hayato Maeda; Md. Golam Rasul; A.K.M. Azad Shah; Chunhong Yuan (Food and Humanity, 2025)

Assessment of Bacteriological Quality and Antibiotic Resistance in Locally and Industrially Produced Ice Creams: A Study on Probiotic Incorporation for Enhanced Safety and Health Benefits in Kushtia City, Bangladesh - Muntaha Binte Mukhles; Abdullah Al Mamun; Md. Khasrul Alam; Md. Amdadul Huq; Md. Abul Kalam Azad; Md. Rasul Karim; M. Mizanur Rahman (Probiotics and Antimicrobial Proteins, 2025)

Crop Classification in Uzbekistan Using Random Forest: Integrating Sentinel-1 SAR and Sentinel-2 Optical Data with Ground-Truth Validation - Azad Rasul (Remote Sensing in Earth Systems Sciences, 2025)

Air pollution exposure and hotspots of CO, NO2, SO2, PM2.5, and aerosols in Iraq - Ajoke Onojeghuo; Azad Rasul; Alex Onojeghuo (Environmental Monitoring and Assessment, 2025)

Assessment and prediction of forest structural attributes in tropical deciduous forests - Pavan Kumar; Prem Chandra Pandey; Azad Rasul; Ramesh K. Ningthoujam (International Journal of Remote Sensing, 2025)

Integrating GIS and remote sensing for spatial distribution assessment of Drought Vulnerability Index - Hasan Mohammed Hameed; Jehan M. Sheikh Suleimany; Azad Rasul (Environmental Monitoring and Assessment, 2025)

Pragmatic investigation of the effect of ether additives on biodiesel combustion to reduce NOx and other harmful emissions - Arun Teja Doppalapudi; Abul Kalam Azad; Md Nurun Nabi; Mohammad G. Rasul; Mohammad Masud Kamal Khan (Fuel, 2025)

Effects of extracting solvents on phytochemical, antioxidant, and antibacterial activity of some seaweeds from the Bay of Bengal offshore Island - Sifat Areefin Emu; Md. Apon Dulal; Tiluttama Das Kali; Mahmuda Sultana Chadni; Md. Golam Rasul; Md. Nurunnabi Mondal; Md. Emranul Ahsan; Murshida Khan; A.K.M. Azad Shah (Food and Humanity, 2023)

Improving Crop Classification Accuracy with Integrated Sentinel-1 and Sentinel-2 Data: a Case Study of Barley and Wheat - Gaylan R. Faqe Ibrahim; Azad Rasul; Haidi Abdullah (Journal of Geovisualization and Spatial Analysis, 2023)

Assessing how irrigation practices and soil moisture affect crop growth through monitoring Sentinel-1 and Sentinel-2 data - Gaylan Rasul Faqe Ibrahim; Azad Rasul; Haidi Abdullah (Environmental Monitoring and Assessment, 2023)

Sentinel‐2 accurately estimated wheat yield in a semi-arid region compared with Landsat 8 - Gaylan Rasul Faqe Ibrahim; Azad Rasul; Haidi Abdullah (International Journal of Remote Sensing, 2023)

Spatial interaction between weather and socio-demographic factor as influencing variables for COVID-19 spread in Iraq - Azad Rasul; Sa’ad Ibrahim (Spatial Information Research, 2023)

Experimental Study of Ambient Air Quality Assessment During Oil Well Drilling - Rawaz Rostam Hamadamin; Luqman Waso Omer; Azad Rasul (Aerosol Science and Engineering, 2022)

Spatial distribution modeling of the wild boar (Sus scrofa) under current and future climate conditions in Iraq - Nabaz R. Khwarahm; Korsh Ararat; Barham A. HamadAmin; Peshawa M. Najmaddin; Azad Rasul; Sarchil Qader (Biologia, 2022)

Snow cover and vegetation greenness with leaf water content control the global land surface temperature - Azad Rasul; Ramesh Ningthoujam (Environment, Development and Sustainability, 2021)

A GIS-based Boolean logic-analytical hierarchy process for solar power plant (case study: Erbil Governorate—Iraq) - Gaylan Rasul Faqe Ibrahim; Arieann Ali Hamid; Umkalthum Mustafa Darwesh; Azad Rasul (Environment, Development and Sustainability, 2021)

A trend of increasing burned areas in Iraq from 2001 to 2019 - Azad Rasul; Gaylan R. Faqe Ibrahim; Hasan M. Hameed; Kevin Tansey (Environment, Development and Sustainability, 2021)
Wildfires have an important role in the ecological process affecting ecosystems at multiple spatial scales. MCD64A1 500 m burned area product is used in this study to document trends of fire events from 2001 to 2019. The research aims to analyze the trend of burned areas in the country. Iraq is selected as study area of the research because of dramatically increasing the number of fires in the country. The study found that the lowest amount of burned areas were located in the center and southwest, while northeast and north faced most of the fires. The trend of burned areas in Iraq was an increase of 71.7 km 2 per year, and, principally, in the last years, burned areas increased by 1363 km 2 . The most extensive burning areas occurred in the Ninawa Governorate (29%). In 2019, burned areas increased to around eight times compared to the yearly average. During 2019, one of the highest classes which contain burned area is “Cropland, rainfed” with 4366 km 2 burned. High maximum air temperature and wind speed are the main factors that contribute to increasing burned areas; however, high precipitation and air pressure lead to a reducing amount of burned areas. The rapid increase of fires in the country as a result of burn crop field residues will lead to worsening air pollution and likely decrease forest area in the future.

An Investigation into the Location of the Crashed Aircraft Through the Use of Free Satellite Images - Azad Rasul (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2019)

Changes in Physicochemical, Microbiological, and Sensory Properties of Sun-Dried Mystus vittatus During Storage at Ambient Temperature - Bhaskar Chandra Majumdar; Faria Afrin; Md. Golam Rasul; Dinesh Chandra Shaha; A.K.M. Azad Shah (Fishes, 2018)
The objective of this study was to investigate the changes in physicochemical, microbiological, and sensory properties of sun-dried Mystus vittatus during storage at ambient temperature. The fish was dried under sun exposure on bamboo mats for 5–6 days until the moisture content reduced to approximately 10–15%. The dried fish was then packed into airtight polyethylene bags and stored at ambient temperature (24 to 29 °C) for 90 days. The physical and sensory properties revealed that the dried fish was acceptable for human consumption for up to 60 days. The pH value slightly decreased from 6.42 to 5.95 during the storage period. The moisture content increased significantly (p

Biochemical, Microbiological, and Sensory Properties of Dried Silver Carp (Hypophthalmichthys molitrix) Influenced by Various Drying Methods - Md. Golam Rasul; Bhaskar Chandra Majumdar; Faria Afrin; Mohammad Abu Jafor Bapary; A.K.M. Azad Shah (Fishes, 2018)
An experiment was performed to evaluate the effects of different drying methods with different pre-treatments on the physico-chemical, microbiological, and sensory properties of the silver carp, Hypophthalmichthys molitrix. In order to achieve this objective, the collected fresh fish were dried using traditional (without any pre-treatment), improved (fish soaked in a 5% salt solution for 10 min and then treated with chili powder (0.3%) and turmeric powder (0.3%)), and solar tunnel (fish soaked in a 5% salt solution for 10 min) drying methods. The results showed that the dried fish produced by the solar tunnel drying method were rehydrated more rapidly than the products produced by the traditional and improved drying methods. The moisture content of the dried H. molitrix was varied from 18.24 to 25.43% on a fresh matter basis. There was no significant (p > 0.05) difference found regarding the protein, lipid, and ash content among the different drying methods on a dry matter basis. The total volatile base nitrogen (TVB-N) contents ranged between 37.58 and 45.03 mg/100 g, and significantly (p

Effect of small proportion of butanol additive on the performance, emission, and combustion of Australian native first- and second-generation biodiesel in a diesel engine - Md. Mofijur Rahman; Mohammad Golam Rasul; Nur Md Sayeed Hassan; Abul Kalam Azad; Md. Nasir Uddin (Environmental Science and Pollution Research, 2017)

Applying a normalized ratio scale technique to assess influences of urban expansion on land surface temperature of the semi-arid city of Erbil - Azad Rasul; Heiko Balzter; Claire Smith (International Journal of Remote Sensing, 2017)